Implementasi Sistem Informasi Ketertelusuran Berbasis RFID Dalam Peningkatan Nilai Saing Produk Pertanian High Involvement - Amadea, Ida Bagus Neo Kurnia; Gunawan, Putu Wida; Tonyjanto, Christian (Prodi Sistem Informasi Universitas Dharma Andalas, 2024)
An effective traceability information system for agricultural products, especially for products with a high level of involvement (High Involvement Products), is very important and urgent to implement. Currently, around 60% of information is lost in every agricultural product supply chain, making it difficult for consumers to recognize which products to buy, which complicates their decision-making process. This research designs and implements a traceability information system for superior varieties of durian fruit, which is considered an agricultural product with a high level of involvement. This research develops the existing traceability system model design, implementation and integration of RFID technology into the system, and analyzes the increase in competitiveness after implementing a traceability information system for agricultural products. The research results show that the model design and implementation of an RFID-based traceability information system can be carried out using RFID tags, with an information loss rate reaching 0% in each supply chain entity. Statistical analysis shows that durian that uses an RFID-based information system has higher competitiveness than durian that does not use an RFID-based (conventional) information system.